2005
DOI: 10.1124/jpet.105.086405
|View full text |Cite
|
Sign up to set email alerts
|

VPAC2Receptors Mediate Vasoactive Intestinal Peptide-Induced Neuroprotection against Neonatal Excitotoxic Brain Lesions in Mice

Abstract: Prepro-vasoactive intestinal peptide (VIP) mRNA codes for two neuropeptides: VIP and peptide histidine isoleucine (PHI). Two VIP receptors, shared with a similar affinity by pituitary adenylate cyclase-activating polypeptide (PACAP), have been cloned: VPAC 1 and VPAC 2 . PHI binds to these receptors with a lower affinity. VPAC receptors are classically associated with a cAMP-dependent pathway, although other pathways, including calcium mobilization and protein kinase C activation have been described. We previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Excitotoxic doses of glutamate also substantially increase PACAP mRNA expression, and the PACAP receptor antagonist PACAP(6 -38) exacerbates the deleterious effect of glutamate . Attenuation by PACAP of glutamate-induced neurotoxicity has also been reported in cultured retinal neurons (Shoge et al, 1999) and in neonatal brain lesions (Rangon et al, 2005;Favrais et al, 2007). Most of the actions of PACAP on cortical neurons are mediated through the cAMP pathway (Martin et al, 1995;Morio et al, 1996), although it has been reported that PACAP can directly modulate NMDA receptors independently of intracellular second messengers Madsen, 1997, 1998).…”
Section: Kip2mentioning
confidence: 92%
“…Excitotoxic doses of glutamate also substantially increase PACAP mRNA expression, and the PACAP receptor antagonist PACAP(6 -38) exacerbates the deleterious effect of glutamate . Attenuation by PACAP of glutamate-induced neurotoxicity has also been reported in cultured retinal neurons (Shoge et al, 1999) and in neonatal brain lesions (Rangon et al, 2005;Favrais et al, 2007). Most of the actions of PACAP on cortical neurons are mediated through the cAMP pathway (Martin et al, 1995;Morio et al, 1996), although it has been reported that PACAP can directly modulate NMDA receptors independently of intracellular second messengers Madsen, 1997, 1998).…”
Section: Kip2mentioning
confidence: 92%
“…Surprisingly, VIP-induced neuroprotection was not mimicked by a large range of doses of PACAP 27 or PACAP 38 [27,31]. This atypical pharmacology of VIP-induced neuroprotection in P5 mice raised several hypotheses: i) activation of PAC 1 receptors could have a toxic effect on the excitotoxic lesions while activation of VPAC receptors could be neuroprotective, leading to a lack of detectable effect for PACAP.…”
Section: Vip Neuroprotective Effects Are Mediated By Vpac2 Receptors mentioning
confidence: 99%
“…VIP effects on white matter were mimicked with a similar potency by VPAC 2 agonists and PHI but not by VPAC 1 agonists [30,31]. Surprisingly, VIP-induced neuroprotection was not mimicked by a large range of doses of PACAP 27 or PACAP 38 [27,31].…”
Section: Vip Neuroprotective Effects Are Mediated By Vpac2 Receptors mentioning
confidence: 99%
See 1 more Smart Citation
“…Both VIP and PACAP, as well as their receptors, have a widespread distribution. A wide array of potential functions of VIP/ PACAP system has been demonstrated, including regulation of circadian rhythm (Harmar et al, 2002), neuronal survival (Rangon et al, 2005), tumor progression (Moody and Gozes, 2007;Valdehita et al, 2009), immune responses (Goetzl et al, 2001;Gonzalez-Rey et al, 2006), metabolic homeostasis (Tsutsumi et al, 2002), and megakaryocyte maturation (Freson et al, 2008). VPAC 2 knockout mice showed loss of electrical rhythmicity in suprachiasmatic neurons in the brain and a reduced behavioral circadian rhythm (Harmar et al, 2002).…”
mentioning
confidence: 99%